African American Women and Obesity Through the Prism of Race. (June 2018) - Knox-Kazimierczuk, Francoise; Geller, Karly; Sellers, Sherrill; Taliaferro Baszile, Denise; Smith-Shockley, Meredith
Background . There are minimal studies focusing on African American women and obesity, and there are even fewer studies examining obesity through a critical race theoretical framework. African American obesity research has largely focused on individual and community interventions, which have not been sufficient to reverse the obesity epidemic. Purpose . The purpose of this study was to examine the relationship between race and body mass index (BMI) for African American women. Method . Previously collected data from the National Survey of American Life Self-Administered Questionnaire, 2001-2003 (NSAL-SAQ) was analyzed for this study. The NSAL-SAQ dedicated a section to the exploration of group and personal identity, along with having anthropometric data and health habit questions to be able to conduct analyses for associations between the racial identity dimensions and obesity. Results . Multiple linear regression was used to examine the constructs of racial identity on BMI comparing standardized coefficients (β) and R 2 adj values. Results indicated participants ascribing more to the stereotype of "Blacks giving up easily" (β = 0.527, p = .000) showed an increased BMI. Additionally, the negative stereotype of "Blacks being violent" (β = 0.663, p = .000) and "Blacks being lazy" (β = 0.506, p = .001) was associated with an increased BMI. Conclusions . Based on these finds high negative racial regard is associated with increased weight. This study contributes uniquely to the scientific literature, focusing on the construct of racial identity and obesity in African American women.